Investigation of the Effect of 9-Week Strength and Endurance Training on the Aerobic Performance in Female Basketball Players - Murat Bekleyiş Apaydın; Emin Süel; Hacı Ahmet Akkaya (ümit doğan üstün, 2021)
This study aimed to investigate the effect of a 9-week strength and endurance training on the aerobic performance of female basketball players. The study group consisted of athletes (n=15 mean age=16±0.7) who are actively competing in the basketball development league (BGL). Before any assessment informed consent form obtained from the parents of the athletes. In the study, additional strength (10 days) and endurance (20 days) trainings were applied to the existing basketball trainings for 9 weeks. The 30-15 Interval Fitness Test was applied to the athletes in different time periods, 9 weeks before and after the program, and the data were recorded statistically. In the study, as the data showed a normal distribution parametric statistical tests were used. As a result of the study, it was found that there was a significant difference p<0.05 in the values ​​of running distance and maximum aerobic speed (MAS), as well as significant differences in the body weight, body mass index and height of the athletes.